KAJIAN KELAYAKAN RELE DIFERENSIAL TRANSFORMATOR MICOM P645 MENGGUNAKAN RTDS - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
To maintain power transformers needed security from tampering. One of these is differential relays. In these case that will be studied is the transformer differential relay MiCOM P645 by using RTDS to result showed the feasibility of the differential relay.Where control through software RSCAD. Detection function activated includes diferential function, the function of limited soil disturbance ( REF ) and impaired function CT when saturation.